Computed tomographic and magnetic resonance imaging of a coup contrecoup traumatic brain injury in a horse. (19th February 2021) - Morgan, R. E.; Dunkel, B.; Spiro, S.; Beltran, E.
Summary: A 3‐year‐old Thoroughbred mare found recumbent in the field was referred for further assessment with suspicion of a skull fracture. Neurological examination identified compulsive tight circling to the left, and hypermetria in all four limbs. The mare was obtunded, with a mild head tilt to the right, absent menace response of the right eye and decreased facial sensation on the right. Standing computed tomographic examination revealed a subtle depression fracture of the dorsal calvarium and moderate intra‐axial midline shift consistent with a traumatic brain injury (TBI). Despite supportive treatment, the mare deteriorated and was subjected to euthanasia. Post‐mortem high field magnetic resonance imaging revealed findings consistent with a small cerebral contusion adjacent to the fracture site, and moderate to severe ipsilateral cerebral oedema within the caudal cerebrum and rostral brainstem, consistent with a coup contrecoup TBI. Brainstem lesions indicate a poor prognosis and support the decision for euthanasia. This is the first report of the imaging findings of a coup contrecoup TBI in a horse.